HUBUNGAN PENGANGGURAN DENGAN PENDAPATAN NASIONAL DAN INFLASI - Azzah Khoirunisa Zasry; Hendra Riofita (STKIP Subang, 2026)
Unemployment, national income, and inflation are key indicators in macroeconomic analysis that are interrelated. This study aims to analyze the relationship between unemployment, national income, and inflation and their implications for economic stability. The method used is a descriptive qualitative approach through literature study from various scientific sources. The results show that unemployment has a negative relationship with national income, where an increase in unemployment reduces economic output. In addition, there is a relationship between unemployment and inflation explained by the Phillips curve, which shows a short-term trade-off between inflation and unemployment. Therefore, appropriate economic policies are needed to maintain a balance between economic growth, price stability, and employment opportunities.